Does physical ill-health increase the risk of suicide? A census-based follow-up study of over 1 million people. (2020) - Onyeka, I. N.; Maguire, A.; Ross, E.; O'Reilly, D.
Abstract: Aims: Mental ill-health is a known risk factor for suicide mortality. However, the relationship between physical ill-health and suicide is less clear. This study examined the relationship between different aspects of physical ill-health and the risk of suicide death. Methods: Data for 1 196 364 adults (aged 18 years and over) were identified from the 2011 Northern Ireland Census and linked to death registrations until the end of 2015. Multivariate logistic regression was used to construct models to test associations with likelihood ratio tests for interactions. Results: Over one in eight individuals (13.7%) reported multimorbidity (⩾2 physical health conditions) and one in four (25.4%) identified having limitation of daily activities. During follow-up, 51 672 individuals died; 877 due to suicide. The gradient in suicide risk by number of physical conditions disappeared following adjustment for activity limitation. Individuals with a lot of activity limitation were over three times more likely to die by suicide (OR = 3.13, 95% CI 2.50–3.93) compared to those with no limitations though this was reduced to OR = 1.72 (95% CI 1.35–2.20) with adjustment for poor mental health. The relationship between activity limitation and suicide was most pronounced at younger ages (18–34 years). Conclusions: This study suggests that it is the effect that physical illness has on a person's life, in terms of disruption to daily activity, rather than the number of conditions that predicts suicide risk, especially at younger ages. Improved awareness and better management of mental wellbeing of individuals with physical health conditions may help to reduce suicides, especially in younger people.